The evaluation of the accuracy of a wireless electronic apex locator in primary molar teeth - Aysenur Oncu; Ecem Sisko; Akif Demirel; Berkan Celikten (BMC Oral Health)
Abstract Background The working length determination is necessary before root canal shaping, chemical cleaning, disinfection, and obturation in pulpectomy of primary dentition. This study aimed to evaluate the accuracy of Wirele-X and compare it with DentaPort ZX and Woodpex III in primary molar teeth. Methods The in vitro study was performed by using 30 extracted primary mandibular molar teeth. In distal roots, the actual working length was determined by taking forward a #10 K-type canal file under a dental operating microscope with 10x magnification. Each tooth and lip clip were embedded in alginate before determining the working lengths using electronic apex locators. The average of three electronic working lengths was calculated for each sample, and the actual working length was subtracted from the electronic working length. Results There were no significant differences in the accuracy rate of DentaPort ZX, Wirele-X, and Woodpex III in the determination of the working length set at ± 0.5 mm and ± 1 mm, respectively (P > 0.05). Conclusions This study reported that DentaPort ZX, Wirele-X, and Woodpex III can be safely used in the pulpectomy of primary molars. Wirele-X can provide an advantage in working length determination in children because of its wireless feature.